PEMBERIAN SANKSI ADMINISTRASI DISIPLIN PEGAWAI NEGERI SIPIL DI DINAS PERTANIAN TANAMAN PANGAN PROVINSI BALI - Junantara, I Made Arya; Pemayun, Cok Istri Anom; Satyawati, Ni Gusti Ayu Dyah (Kertha Wicara : Journal Ilmu Hukum; Vol 1 No 01 (2012))
Government employees are the public servants who faithfully on Pancasila, theConstitution of the republic of Indonesian 1945 and the government and united, wellminded, disciplined, dignified, efficient, high quality and are aware of itsresponsibilities to the state. In an effort to improve the discipline of government havemade the civil government regulation. In the government regulation amended byGovernment Regulation Number.53 of2010 on Civil Servant Discipline. Civil ServantsDisciplinary Rules are rules governing the obligations, prohibitions, and penalties ifobligations are not complied with or violated by the Civil Servant. However ,from theyears 2010-2011increaseddisciplinarycivil servant in the Department of Food Crops ofBali. Most of the in disciplinary is because of the internal factor of the civil servantdaily.
Keywords: Civil, Administrative Sanction Discipline, Discipline Granting Administrative Sanctions.